Film Formation from Nanosized Copolymeric Latex Particles: A Photon Transmission Study - Arda; Özer; Pişkin; Pekcan (Elsevier BV, 2001)
The photon transmission technique was used to monitor the evolution of transparency during film formation from nanosized copolymeric latex particles. The latex films were prepared from poly(methyl methacrylate-co-butyl methacrylate) (P(MMA-co-BMA)) particles which were produced by microemulsion polymerization. These films were annealed at elevated temperatures in various time intervals above the glass transition temperature (T(g)) of P(MMA-co-BMA). It is observed that the transmitted photon intensity (I(tr)) from these films increased as the annealing temperature increased. There are three different film formation stages. These stages are explained by the void closure, healing, and interdiffusion processes, respectively. The activation energies for viscous flow (DeltaH approximately 16 kcal/mol), minor chains (DeltaE(H) approximately 27 kcal/mol), and backbone motion (Delta E(b) approximately 132 kcal/mol) were obtained using various models. Void closure (tau(v), T(v)) and healing points (tau(H), T(H)) were determined. Using the time-temperature pairs, void closure and healing activation energies were measured and found to be 21 and 30 kcal/mol, respectively. Copyright 2001 Academic Press.